696 Brentuximab vedotin, a CD30-directed antibody-drug conjugate, selectively depletes activated Tregs in vitro and in vivo. (10th December 2020) - Grogan, Bryan; James, Reice; Ulrich, Michelle; Gardai, Shyra; Heiser, Ryan; James, Reice
Abstract : Background: Regulatory T cells (Tregs) play an important role in maintaining immune homeostasis, preventing excessive inflammation in normal tissues. In cancer, Tregs hamper anti-tumor immunosurveillance and facilitate immune evasion. Selective targeting of intratumoral Tregs is a potentially promising treatment approach. Orthogonal evaluation of tumor-infiltrating lymphocytes (TILs) in solid tumors in mice and humans have identified CCR8, and several tumor necrosis family receptors (TNFRs), including TNFSFR8 (CD30), as receptors differentially upregulated on intratumoral Tregs compared to normal tissue Tregs and other intratumoral T cells, making these intriguing therapeutic targets.Brentuximab vedotin (BV) is approved for classical Hodgkin lymphoma (cHL) across multiple lines of therapy including frontline use in stage III/IV cHL in combination with doxorubicin, vinblastine, and dacarbazine. BV is also approved for certain CD30-expressing T-cell lymphomas. BV is comprised of a CD30-directed monoclonal antibody conjugated to the highly potent microtubule-disrupting agent monomethyl auristatin E (MMAE).The activity of BV in lymphomas is thought to primarily result from tumor directed intracellular MMAE release, leading to mitotic arrest and apoptotic cell death.The role CD30 plays in normal immune function is unclear, with both costimulatory and proapoptotic roles described. CD30 is transiently upregulated following activation of memory T cells and expression has been linked to highly activated/suppressive IRF4+ effector Tregs. Methods: Here we evaluated the activity of BV on CD30-expressing T cell subsets in vitro and in vivo. Results: Treatment of enriched T cell subsets with clinically relevant concentrations of BV drove selective depletion of CD30-expressing Tregs > CD30-expressingCD4+ T memory cells, with minimal effects on CD30-expressing CD8+ T memory cells. In a humanized xeno-GVHD model, treatment with BV selectively depleted Tregs resulting in accelerated wasting and robust T cell expansion. The observed differential activity on Tregs is likely attributable to significant increases in CD30 expression and reduced efflux pump activity relative to other T cell subsets. Interestingly, blockade of CD25 signaling prevents CD30 expression on T cell subsets without impacting proliferation, suggesting a link between CD25, the high affinity IL-2 receptor, and CD30 expression. Conclusions: Together, these data suggest that BV may have an immunomodulatory effect through selective depletion of highly suppressive CD30-expressing Tregs. Acknowledgements: The authors would like to thank Michael Harrison, PharmD for their assistance in abstract preparation. Ethics Approval: Animals studies were approved by and conducted in accordance with Seattle Genetics Institutional Care and Use Committee protocol #SGE-024.